Historical Significance of the Nan River Basin before A.D. 1855: City Products and Multicultural Society - Prommas, Teeraporn; Kongklin, Wilubon (Parichart Journal, 2024)
This academic article aimed to study the historical significance of the Nan River Basin before A.D.1855, focusing on the explanation of the Nan River in terms of the city’s origin, products-gathering points and production facilities center, and the origin of multicultural society. The result indicated that the geography of the Nan River was important as a product-gathering center leading to trading and giving raise to the cities along the Nan River. The cities were Mueang Pua, Mueang Tha Pla, Mueang Thung Yang, Mueang Fang, Mueang Phichai, Mueang Phitsanulok, Mueang Chat Trakran, Mueang Nakhon Thai, Mueang Phichit, and Mueang Nakhon Sawan. These diversities led to the multicultural society of the Nan River. Moreover, understanding the historical significance of the Nan River helped visualize the effort of policy formulation from the governments in order to have the authority to intervene in the affairs of the Nan River.